HUMANITARIAN LAW AND ASEAN: ANALYZING REGIONAL COMMITMENT AND HUMANITARIAN RESPONSE MECHANISMS IN SOUTHEAST ASIA - Marah, Thomas Sheku (Journal of Governance and Public Administration, 2025)
This paper analyzes the significance and role of the Association of Southeast Asian Nations (ASEAN) within the domain of International Humanitarian Law (IHL) in Southeast Asia. In particular, in a region often susceptible to natural disasters, internal conflicts, and humanitarian crises, the work of ASEAN to promote the prescriptions of IHL is increasingly essential. Using a qualitative doctrinal legal research methodology, the paper analyzes ASEAN's legal tools (e.g., AADMER), institutional framework (e.g., the AHA Centre), and engagement with international humanitarian actors. From primary legal sources, scholarly literature, and case studies—the Rohingya crisis, regional pandemic response—the paper examines ASEAN's adherence to IHL norms. Despite institutional advances in areas like disaster management, the research discovers that the norms of non-interference, lack of binding enforcement mechanisms, and differential commitment of state actors are major challenges to ASEAN’s effectiveness. The paper, in a concluding section, provides suggestions on how compliance with IHL can be improved, including through law reform, expanding the mandates of relevant ASEAN institutions, and increased cooperation with international humanitarian actors.